Kepastian Hukum di Bidang Perpajakan yang Berbasis Cita Hukum Pancasila - Sinaga, Henry Dianto P. (Journal of Tax Law and Policy, 2023)
The power of law in books tradition of tax law, whereas every applicable law in Indonesia must contain the meaning of Pancasila, has created disputes between taxpayer and tax authority. So that the legal certainty of tax law not only must be reconceptualized from only the lex scripta, lex certa, and lex stricta system, but also with the certainty of the legal values that can always be associated with the grundnorm of Pancasila by sticking to the creed that the law is used for human development on a regular basis. In order to generate the reconceptualization of legal certainty based on the ideology of Pancasila, needed the priority of a priori knowledge of all tax apparatus that can interpret tax law with the universal truth based on five principles of Pancasila. It is suggested to regulate the tax legal certainty definition in the future tax law reform, which can minimize tax disputes.